Dynamic Decrease in Eosinophil After Intravenous Thrombolysis Predicts Poor Prognosis of Acute Ischemic Stroke: A Longitudinal Study - Yang, Dehao; Huang, Honghao; Weng, Yiyun; Ren, Junli; Yang, Chenguang; Wang, Jianing; Gao, Beibei; Zeng, Tian; Hu, Jingyu; Pan, Wenjing; Sun, Fangyue; Zhou, Xinbo; et al. (Frontiers in Immunology, 2021)
Background and Purpose Blood eosinophil counts are thought to be associated with atherosclerosis in acute ischemic stroke (AIS) and AIS severity. We aimed to investigate 1): the temporal profile of eosinophil in AIS patients treated with recombinant tissue plasminogen activator (r-tPA); 2): The association between dynamic eosinophil and 3-month outcomes in different AIS etiologies; 3): incremental predictive ability of dynamic eosinophil adding to conventional model; and 4): the longitudinal change of neutrophil-to-lymphocyte ratio (NLR) and compared its prognostic value with eosinophils. Methods A total of 623 AIS patients with intravenous thrombolysis in two hospitals were included. Blood samples were obtained on admission, within 24 h after an intravenous thrombolysis and on the seventh day. A multivariate logistic regression model with restricted cubic spline was performed to explore the association between dynamic eosinophil and a 3-month poor outcome. C-statistic, net reclassification improvement (NRI) and integrated discrimination improvement (IDI) were adopted to explore the incremental predictive ability. Results Percent change in eosinophil counts after intravenous thrombolysis was median −25.00% (IQR −68.25%–+14.29%). Decrease in eosinophil >75% after intravenous thrombolysis was associated with 2.585 times risk for poor outcome and 13.836 times risk for death. However, the association were weak for patients outside of cardioembolic stroke. Adding eosinophil changes to a conventional model improved the discriminatory ability of poor outcome (NRI = 53.3%; IDI = 2.2%) and death (NRI = 101.0%; IDI = 6.9%). Conclusions Dynamic decrease in eosinophil after intravenous thrombolysis predicts a 3-month poor outcome and death in AIS patients with r-tPA treatment and improved the predictive ability of conventional model. However, this result needs to be interpreted carefully in non-cardioembolic AIS patients.